Inovasi Media Pembelajaran Bahasa dan Sastra Indonesia untuk Meningkatkan Kreativitas Belajar Siswa Madrasah Ibtidaiyah - Haryono Haryono; Abdul Wachid Bambang Suharto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
Teachers must be able to make various innovations in learning. One of the innovations that can be made is in learning media in order to foster student learning motivation. Learning media is an important component in improving the quality of interaction between teachers and students and between students and their learning environment. Teachers must have good skills in choosing and using learning media. This study aims to describe and analyze audio, visual, and audio-visual media innovations in learning the Indonesian language and literature to improve student learning creativity at MI Ma'arif NU 1 Sokanegara Purbalingga. To obtain the data, the researcher used observation, interview, and questionnaire techniques. Data analysis was done qualitatively. The results showed that teachers at MI Ma'arif NU 1 Sokanegara Purbalingga had already innovated in learning media. The media used can function well in the learning process and can stimulate students' imagining and thinking so that students are able to issue new ideas according to the learning theme. The media most often used by teachers in learning is audio-visual media. This medium is able to increase students' creativity because of its convenience, transparency, objectivity, and flexibility.